A preferential switch between placental GR exon 1 promoter variants in the presence of maternal asthma or inflammation upregulates GRα D isoforms. (May 2021) - Saif, Zarqa; Meakin, Ashley S.; Clifton, Vicki L.
Abstract: Introduction: The human placenta expresses multiple glucocorticoid receptor (GR) isoforms that may be partially regulated by the untranslated 5' exon 1 GR gene promoter region which consists of 9 different promoters and 13 splice variants. The objective of this study was to determine which GR exon 1 variants are expressed in the human placenta and relate these findings to GR mRNA and protein expression. Methods: Placental extracts from pregnancies with or without the complication of maternal asthma and trophoblast cells exposed to an inflammatory challenge in vitro were examined using PCR and Western blot to measure GR exon 1 variants, GR splice variant mRNA and GR protein isoforms, respectively. Results: All 9 GR exon 1 variants were detectable in the human placenta and included GR exons 1A, 1B, 1C, 1D, 1E, 1F, 1H, 1I and 1J. In the presence of maternal asthma and a male fetus there was preferential expression of GR exon 1B, 1C, IF and 1J (KW-ANOVA, P < 0.05) which were positively correlated with GRα D3 protein isoform. In female placentae from pregnancies complicated by asthma there was no upregulation of any exon 1 variant (KW-ANOVA, P < 0.05). Exposure of BeWo trophoblast cell line to an inflammatory challenge, lipopolysaccharide, in vitro, resulted in preferential expression of GR exon 1B, 1D, 1E and 1H and associated with GRα-D1 protein upregulation. Discussion: The preferential expression of different GR exon 1 promoters drive the upregulation of GRα D isoforms and contribute to glucocorticoid resistance observed in male placentae of pregnancies complicated by asthma. Highlights: All 9 GR exon 1 variants were detectable in the human placenta. There was differential expression of GR exon 1 variants in the presence of asthma and a male. Inflammation resulted in upregulation of GR exon 1B, 1D, 1E and 1H and GRα-D1 protein.